Echinoderm Biodiversity and Biogeography in Oceanic Islands: the Azores as a case study - Madeira, Patrícia Gomes Antunes (2020)
Oceanic Islands are natural laboratories for the study of the processes and patterns of dispersion, colonization and ultimately of the appearance of new species. In the Northeast Atlantic, the archipelago of the Azores meets all the requirements to be considered one of the most isolated oceanic island systems. In general terms, the Azorean biota, as other oceanic systems, derives from dispersal chance events. For shallow-water marine benthic organisms, the main mechanisms to overcome the isolation by distance are rafting by non-planktonic life stages and through planktonic larval stages, both of which rely heavily on sea-surface currents to travel. However, and in spite of being under the influence of the western-intensified Gulf Current, the Azorean biota shows an opposite trend, being predominantly derived from the NE Atlantic and the Mediterranean. This apparent paradox has startled many marine biogeographers, who search for answers in the present-day faunal patterns together with those reconstructed through the past geological history of the archipelago. The present study attempts to further contribute to the knowledge of the marine fauna of the Azores, and its biogeographical relationships, using the echinoderms as a model. This animal phylum encloses a diverse group of strictly marine invertebrates found at all latitudes and depths. Furthermore, the echinoderms form one of the most conspicuous elements of both shallow- and deep-sea fauna in the Azores, and both in extant waters and among the fossiliferous outcrops of Santa Maria (37°N23’ 24°45’W), the oldest island in the archipelago. Thus, for a clear biogeographical background it was necessary to construct an updated catalogue of both local extant and fossil echinoderm fauna. During the International Workshops ‘Palaeontology in Atlantic Islands’, held in Santa Maria Island between 2002-2013, new material was collected from Lower Pliocene and Pleistocene deposits. The early Pliocene beds encompass the following taxa: Eucidaris tribuloides, Echinoneus cf. cyclostomus, Clypeaster altus, Echinocyamus pusillus, Echinocardium sp. 1, Echinocardium sp. 2, Schizobrissus sp. and undetermined spatangoids. The Pleistocene outcrops (MISS 5e) included three regular echinoid species, Sphaerechinus granularis, Arbacia lixula and Paracentrotus lividus. The small irregular echinoid Echinocyamus pusillus was also present in the Azorean Pleistocene fauna, a species common as well in the extant coasts of the archipelago. The presence of tropical taxa in the early Pliocene sediments clearly contrasts with the warm temperate taxa found in the Pleistocene and present coasts of the Azores. Updated faunal lists are fundamental in biodiversity and biogeographical studies. Arbaciella elegans is a small cryptic echinoid species that was believed to have a large geographical range from the tropical Atlantic waters of Central Africa to the northern shores of the Azores, Canaries, Northwest Africa and Mediterranean Sea. However, and unlike the Central African material, individuals from the warm temperate waters present a uniform dark color. A morphological and genetic characterization of specimens from the Azores shows that the dark Arbaciella phenotype represents in fact juvenile stages of Arbacia lixula, which implies that A. elegans is circumscribed to the tropical African waters from where it was first described. This study emphasizes the difficulty of constructing faunal lists mirroring true distributions of species or local biodiversity, when rare or cryptic species are involved. The Faculty of Sciencie and Tecnology (University of the Azores), houses hundreds of echinoderm specimens collected over more than 20 years of activity by the former Department of Biology. Three young specimens of the Mediterranean sea star Sclerasterias richardi (Perrier, in Milne-Edwards, 1882), a species previously not known to the Azores, were found among the echinoderm material. These animals were dredged off the south coast of São Miguel Island, at 135 m depth. Sclerasterias richardi is one of two sea star species known to reproduce asexually through fission in the Azores, the other being the shallow-water Coscinasterias tenuispina (Lamarck, 1816). However, S. richardi, though a shelf species, lives at much deeper waters than the latter. S. richardi is also capable of producing long-lived planktotrophic larvae with high dispersal potential to reach remote areas such as the Azores. The presence of S. richardi in Azorean waters in an otherwise thoroughly investigated area does not necessarily imply a recent arrival, as the depths in consideration (80-700 m) are also the least studied in the archipelago. The review of the extant echinoderm fauna of the Azores, based on the related bibliography that has been accumulating over 150 years, complemented with the construction of an important local echinoderm reference collection in the University of the Azores, resulted in a critical reassessment of this significant component of the Azorean marine fauna. Herein are reported 172 species of echinoderms (6 crinoids, 55 ophiuroids, 45 asteroids, 36 holothuroids and 30 echinoids) to the archipelago, most of them inhabiting deep-waters. Although 65 species could be classified as shelf species (<200 m), only 29 occur in shallow-water (≤50 m depth). In general, the echinoderm species from the Azores are characterized by a wide geographical distribution in the Atlantic Ocean, with an additional 37 species occurring as well outside the Atlantic. Only 9 taxa (all deep-water species, >840 m) appear to be restricted to the Azorean waters. Though relatively poorer in number of species, the Azores show similar general trends to what is observed in other Macaronesian archipelagos (i.e. Madeira, Canaries and Selvagens): lack of endemic species, dominance of echinoderm fauna generally associated with rocky shores and species capable of producing planktonic feeding larvae. The relatively low echinoderm diversity could be attributed to the archipelago remoteness, the northern geographical position and to other local features attributed to their relative young volcanic age (e.g., lower habitat diversity). The echinoderm fauna of the Azores encompasses several edible species, though none known to be traditionally harvested. In recent years, fisheries targeting holothurian species have developed dramatically in several European and North African countries, and two of the most common sea-cumber species in the Azores, Holothuria mammata and H. sanctori, are now being commercially harvested in the Northeast Atlantic and in the Mediterranean Sea. The identification of Holothuria species tends to be difficult and time-consuming, and in many cases requires experienced taxonomists. Conversely, the use of PCR-RFLPs to rapidly and inexpensively identify species with no need for taxonomical or genetic expertise could prove a valuable asset. The present work introduces a simple and fast method, using restriction nuclease Sau3AI on 16S rRNA fragments. A simple non-destructive DNA sampling is also presented, using tube feet or oral tentacles, to be applied in genetic studies. The updated faunal list of the echinoderms of the Azores was combined with those from the other areas in an updated distributional catalogue of the shallow-water echinoderms (≤200 m depth) from the North and Central Atlantic, and the Mediterranean Sea, providing the basic framework for the analysis of biodiversity patterns and the construction of a biogeographical model. A total of 891 species belonging to 341 genera of shallow-water echinoderms are presently recorded in the studied areas. The tropical West Atlantic was by far the most biodiverse region (483 species, 210 of which were endemic). The Mediterranean Sea did not emerge as a biodiversity hotspot, revealing similar biodiversity rates as the neighbouring regions of Iberian and NW Africa, but presented significant endemism rate. Among the insular systems, Canaries presented the highest echinoderm biodiversity with 85 species, followed by Cabo Verde with 76. A positive correlation between latitude and the species’ depth range was detected, confirming the Rapoport’s latitudinal gradient. The most common larval development was planktotrophic (119 species), followed by the lecithotrophic (71 species) and aplanktonic (47 species). The relative representation of lecithotrophic and aplanktonic larval development increased towards high latitude areas and decreased as species geographical range increased. Also, the asexual reproduction decreased towards high latitude colder areas and this reduction was correlated with the relative increase of aplanktonic larval mode of development in the same areas. Endemic species were particularly numerous among sediment-associated habitats and broadly distributed species showed no preference for either soft or hard bottoms. Most areas showed a natural decrease of shared species with increasing geographical distance and this was particularly evident in oceanic systems. In these, faunal affinities tended to be related with the nearest continental shores, regardless of the prevailing sea-surface currents. In general, echinoderms proved to be good models for testing biodiversity and biogeographical patterns, though significant gaps were found on the available information.